Why Rural Matters 2003: The Continuing Need For Every State to Take Action on Rural Education - Elizabeth Beeson; Marty Strange (Journal of Research in Rural Education, 2003)
Nearly one in three of America's school-age children attend public schools in rural areas or small towns of less than 25,000, and more than one in six go to school inthe very smallest communities, those with populations under 2,500. These children, their schools, and their communities matter, and they deserve more consideration than they get in the national debate over education policy. This report presents and analyzes descriptive data about the rural schools that serve the 21% of our students who go to school in communities of under 2,500.